Simulation and Optimization of Furnaces and Kilns for Nonferrous Metallurgical Engineering - Mei, Chi.; Peng, Xiaoqi; Zhou, Ping.; Zhou, Jiemin; Zhou, Naijun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
"Simulation and Optimization of Furnaces and Kilns for Nonferrous Metallurgical Engineering" is based on advanced theories and research methods for fluid flow, mass and heat transfer, and fuel combustion. It introduces a hologram simulation and optimization methods for fluid field, temperature field, concentration field, and electro-magnetic field in various kinds of furnaces and kilns. Practical examples and a detailed introduction to methods for simulation and optimization of complex systems are included as well. These new methods have brought significant economic benefits to the industries involved. The book is intended for researchers and technical experts in metallurgical engineering, materials engineering, power and thermal energy engineering, chemical engineering, and mechanical engineering. Chi Mei, Jiemin Zhou, Xiaoqi Peng, Naijun Zhou and Ping Zhou are all professors at School of Energy Science and Engineering, Central South University, Changsha, Hunan Province, China.
Modeling of the Thermophysical Processes in FKNME -- Hologram Simulation of the FKNME -- Thermal Engineering Processes Simulation Based on Artificial Intelligence -- Hologram Simulation of Aluminum Reduction Cells -- Simulation and Optimization of Electric Smelting Furnace -- Coupling Simulation of Four-field in Flame Furnace -- Modeling of Dilute and Dense Phase in Generalized Fluidization -- Multiple Modeling of the Singleended Radiant Tubes -- Multi-objective Systematic Optimization of FKNME.
Keywords: Chemical engineering; Structural control (Engineering).; Materials; Materials Science; Metallic Materials; Operating Procedures, Materials Treatment; Industrial Chemistry/Chemical Engineering